Re-initiation of Oral Food Intake Following Enteral Nutrition Alters Oral and Gut Microbiota Communities - Katagiri, Sayaka; Shiba, Takahiko; Tohara, Haruka; Yamaguchi, Kohei; Hara, Koji; Nakagawa, Kazuharu; Komatsu, Keiji; Watanabe, Kazuki; Ohsugi, Yujin; Maekawa, Shogo; Iwata, Takanori (Frontiers in Cellular and Infection Microbiology, 2019)
Stroke is associated with multiple forms of disability, including dysphagia. Post-stroke dysphagia increases the risks of pneumonia and mortality and often results in cessation of oral feeding. However, appropriate rehabilitation methods can eventually lead to resumption of oral food intake. This study tried to clarify that re-initiating oral food intake could modify the composition of oral/gut microbial communities in patients with dysphagia. From 78 patients with sub-acute stage of stroke, 11 complete tube feeding subjects without taking antibiotics were enrolled and received rehabilitation for re-initiation of oral food intake, and 8 subjects were brought back to complete oral feeding. Oral and gut microbiota community profiles were evaluated using 16S rRNA sequencing of the saliva and feces samples before and after re-initiation of oral food intake in patients recovering from enteral nutrition under the same nutrient condition. Standard nutrition in the hospital was 1,840 kcal, including protein = 75 g, fat = 45 g, and carbohydrates = 280 g both for tube and oral feeding subjects. Oral food intake increased oral and gut microbiome diversity and altered the composition of the microbiome. Oral and gut microbiome compositions were drastically different; however, the abundance of family Carnobacteriaceae and genus Granulicatella was increased in both the oral and gut microbiome after re-initiation of oral food intake. Although oral microbiota showed more significant changes than the gut microbiota, metagenome prediction revealed the presence of more differentially enriched pathways in the gut. In addition, simpler co-occurrence networks of oral and gut microbiomes, indicating improved dysbiosis of the microbiome, were observed during oral feeding as compared to that during tube feeding. Oral food intake affects oral and gut microbiomes in patients recovering from enteral nutrition. Rehabilitation for dysphagia can modify systemic health by increasing the diversity and altering the composition and co-occurrence network structure of oral and gut microbial communities.